2002
DOI: 10.1044/1092-4388(2002/048)
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Temporal Processing Performance of Young Adults With Reading Disorders

Abstract: The present study investigated the temporal processing abilities of college students with diagnosed reading disorders. A behavioral test battery was used that involved discrimination of the pattern of presentation of tone triads in which individual components differed in either frequency or duration. An additional test involving measurement of frequency difference limens for long- and short-duration tones was also administered. The college students with reading disorders exhibited significantly higher error ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 38 publications
1
32
1
6
Order By: Relevance
“…First, despite a considerable number of studies reporting impaired frequency discrimination in people with dyslexia, this finding is by no means universal. Walker, Shinn, Cranford, Givens, and Holbert (2002) found that the group difference between adults with dyslexia and controls on a test of frequency discrimination at 1 kHz just failed to reach significance, owing to the high variability of scores within both the dyslexic and the control groups. Further, even studies that show a significant group effect tend to show considerable individual variation in performance, and there is often substantial overlap in scores between groups.…”
Section: Frequency Discrimination and Srd: A Causal Explanation?mentioning
confidence: 98%
“…First, despite a considerable number of studies reporting impaired frequency discrimination in people with dyslexia, this finding is by no means universal. Walker, Shinn, Cranford, Givens, and Holbert (2002) found that the group difference between adults with dyslexia and controls on a test of frequency discrimination at 1 kHz just failed to reach significance, owing to the high variability of scores within both the dyslexic and the control groups. Further, even studies that show a significant group effect tend to show considerable individual variation in performance, and there is often substantial overlap in scores between groups.…”
Section: Frequency Discrimination and Srd: A Causal Explanation?mentioning
confidence: 98%
“…Using these various techniques, studies have found evidence for poor FD in a range of participant groups, from children and adults with dyslexia (Baldeweg et al, 1999; Banai & Ahissar, 2004; Fischer & Hartnegg, 2004; McAnally & Stein, 1996; Schäffler et al, 2004; cf. Walker, Shinn, Cranford, Givens & Holbert, 2002) to remediation‐resistant reading‐impaired children (Cacace et al, 2000), and selected (Ahissar et al, 2000; De Weirdt, 1988) and unselected ‘poor readers’ (Talcott et al, 2002).…”
Section: Frequency Discrimination (Fd) Deficits In Dyslexiamentioning
confidence: 99%
“…In audition, reading-disabled adults and children experience difficulties discriminating the pattern of presentation of tone triads with short durations (Walker, Shinn, Cranford, Givens, & Holbert, 2002), rapidly presented speech sounds (Kraus et al, 1996), and amplitude-modulated (AM) or frequency-modulated (FM) tones (McAnally & Stein, 1996;Witton, Stein, Stoodley, Rosner, & Talcott, 2002). They also display higher fusion points to separate two auditory temporal stimuli (Hari & Kiesilä, 1996;Hautus, Setchell, Waldie, & Kirk, 2003;McCroskey & Kidder, 1980).…”
mentioning
confidence: 99%